Hexagonal Ce1-xLnx(OH)CO3 as Highly Efficient Precursors of Nanocrystalline Ln(III-IV)-Substituted Ceria - Sorbello, Cecilia (2017)
Monophasic hexagonal precursors, obeying to the formula Ce1-xLnx(OH)CO3, are introduced herein as versatile precursors for the preparation of Ln(III-IV)-substituted nanocrystalline ceria. To this aim, three hexagonal Ce1-xLnx(OH)CO3 families increasingly substituted with Ln(III) = Sm(III), Gd(III), or Pr(III), were prepared with high (quantitative) precipitation yields. Once Ce1-xLnx(OH)CO3 precursors are submitted to moderate thermal treatment (5 h, 723 K, air atmosphere), the oxidation of Ce(III) centers triggers a single step massive decomposition (dehydroxylation/decarbonation), developing monophasic Ce1-xLnxO2-δ solid solutions with Ln(IV-III) substitutions up to 30%. These binary oxides exhibit large surface areas, up to 130 m2 g-1, even larger than those obtained by means of costly procedures.